Determinación de los costos de producción y la fijación del precio de venta en la asociación de producción textil hilando con excelencia “ASOPROTHEX” de la provincia de Cotopaxi, cantón Latacunga, durante el tercer trimestre del año 2023 - Carrillo Hurtado, Anabelle Estefanía (2024)
The textile sector in Ecuador ranks as the third most representative income besides being a generator of employment, despite this, it is facing significant challenges in terms of profitability and competitiveness. This situation arises from the lack of proper cost management, particularly within associations dedicated to garment manufacturing in the Cotopaxi province. Cost accounting serves as a tool for senior management, aiding the analysis of efficient use of the resources involved in the production process, in the same sense, various authors mention that the use of a cost system facilitates the control of the impact of the factory load to establish strategies that maximize profitability through accurate determination of manufacturing costs and appropriate pricing. The methodology employed in this project was directed towards a quantitative approach to collect numerical data used in calculating the production cost of the three products: detachable sleeve sweaters, industrials overalls and medical aprons. Observation techniques and questionnaires were used to gather data on the production process and cost management within the association. The analysis of the cost sheet revealed that ASOPROTHEX maintains a high cost in terms of direct raw materials, which must be addressed to become more competitive. Additionally, with all the information collected, the total production cost incurred by the textile association in its various garments could be accurately established. Thus, the unit manufacturing cost for removable sleeve sweaters is $19,87; for industrial overalls $17,46, and for medical aprons is $12,13 to which their percentage of profit was added for sale to the public. The initiative aims to improve the sustainability of small textile organizations facing increasing competition by facilitating decision-making to ensure their continued presence in the market.